Whole-Body Regeneration in Sponges: Diversity, Fine Mechanisms, and Future Prospects - Ereskovsky, Alexander (Genes (Basel), 2021)
While virtually all animals show certain abilities for regeneration after an injury, these abilities vary greatly among metazoans. Porifera (Sponges) is basal metazoans characterized by a wide variety of different regenerative processes, including whole-body regeneration (WBR). Considering phylogenetic position and unique body organization, sponges are highly promising models, as they can shed light on the origin and early evolution of regeneration in general and WBR in particular. The present review summarizes available data on the morphogenetic and cellular mechanisms accompanying different types of WBR in sponges. Sponges show a high diversity of WBR, which principally could be divided into (1) WBR from a body fragment and (2) WBR by aggregation of dissociated cells. Sponges belonging to different phylogenetic clades and even to different species and/or differing in the anatomical structure undergo different morphogeneses after similar operations. A common characteristic feature of WBR in sponges is the instability of the main body axis: a change of the organism polarity is described during all types of WBR. The cellular mechanisms of WBR are different across sponge classes, while cell dedifferentiations and transdifferentiations are involved in regeneration processes in all sponges. Data considering molecular regulation of WBR in sponges are extremely scarce. However, the possibility to achieve various types of WBR ensured by common morphogenetic and cellular basis in a single species makes sponges highly accessible for future comprehensive physiological, biochemical, and molecular studies of regeneration processes.